Comparative Analysis of Chinese and European-American Cervical Vertebrae Geometry - Haibin CHEN; Liying ZHANG; Liwen TAN; Shaoxiang ZHANG; Xuemei CHENG; Zhengguo WANG (Institute of Advanced Engineering and Science, 2012)
To date, many finite element neck models suitable for the European-American population have been proposed to study neck impact injury mechanisms. However, the issue that a Chinese neck model can be obtained using the geometrical scaling of a western model is highly controversial. A Chinese neck model, based on MRI/CT scan images and frozen slice images from a 35-year old male cadaver, was established in this paper to examine the geometrical difference between Chinese and European-American cervical vertebrae. Results showed that at every level of all cervical vertebrae except C2, an evident difference between the geometrical model of the Chinese and European-American cervical vertebrae was revealed. In summary, it is necessary to apply the actual anatomic parameters of the Chinese neck rather than the scaled geometry of the European-American neck to establish a standard mid-size Chinese neck finite element model. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1616